Algunos pensamientos sobre la tormenta que se avecina en las redes sociales, el medio ambiente y la necesidad de un diálogo transformador y democrático - Carr, Paul R. (2021)
This text presents arguments linking together social media, the environment and the need for transformative dialogue. Within the backdrop of overlapping frameworks of democracy, I argue that media manipulation and fake news are not a new phenomenon but that the social media context has complexified the dissemination and sophistication of hegemonic processes that cover all corners of the Globe. Conspiracies underpinning the anti-vax movement, contesting the defeat of President Trump, xenophobia and many others provide some context for how the environment is and can be distorted through viral, urban myth messages, comments, videos, texts and other media within a torrent of anti-science ideology. The text concludes with some thoughts on particular obstacles, implications and consequences as well as innovations that may be helpful in moving meaningful dialogue forward in relation to environmental agency, action and activism.